Balancing National Security And Open Investment: Comparative Study On America’s Foreign Investment Screening Regulation For Indonesia’s Potential Adaptation - Prabangkara, Ali Arva; Yudha Prawira, M. Rizki (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study explores the delicate balance between national security and economic openness in the context of foreign direct investment (FDI), focusing on how Indonesia can potentially adopt a screening mechanism inspired by the United States’ regulatory framework. Using a comparative legal approach, this research analyzes the U.S. Foreign Investment Risk Review Modernization Act (FIRRMA) and the role of the Committee on Foreign Investment in the United States (CFIUS) as a model for assessing foreign investment that may pose national security risks. The study investigates key elements of FIRRMA, such as the scope of covered transactions, strategic sectors, and the national security review process. These aspects are then examined against Indonesia’s current regulatory landscape, highlighting existing gaps in investment screening, especially in sectors critical to national sovereignty and data security. The findings suggest that while Indonesia promotes an open investment climate, the absence of a structured and centralized foreign investment review mechanism exposes the country to vulnerabilities in strategic industries. The paper argues for a context-sensitive adaptation of the U.S. model, proposing a more robust and preventive screening system that upholds national security without discouraging foreign capital inflows. This study contributes to the growing discourse on legal harmonization and institutional readiness in safeguarding national interests amid globalization.